Nervus intermedius meningioma. Issue 6 (June 2014) - Rodgers, B; Chamoun, R; Newell, K; Lin, J
Abstract Objective: To report a case of meningioma arising from the nervus intermedius. Methods: This paper comprises a case report, literature review, and discussion regarding the presentation of a nervus intermedius meningioma, comparing and contrasting this to other relevant neoplasms of the internal auditory canal and cerebellopontine angle. Results: Tumours of the cerebellopontine angle include vestibular schwannomas, facial schwannomas and, more rarely, nervus intermedius schwannomas. The nervus intermedius is a division of the facial nerve at the cerebellopontine angle, with parasympathetic and afferent somatic components. Our patient presented with progressive hearing loss. An ipsilateral internal auditory canal mass at the fundus, as indicated by magnetic resonance imaging and electroneuronography, was suggestive of vestibular schwannoma. Intra-operative dissection revealed a nervus intermedius tumour. Histological evaluation indicated a meningioma rather than a schwannoma. Conclusion: This is the first reported case of meningioma involving the nervus intermedius. The implications this pathology may have on surgical approach, facial nerve outcomes, and the need for improved pre-operative imaging and intra-operative monitoring are discussed. A review of the current literature on nervus intermedius tumour is provided.